Cordillera Negra, de Óscar Colchado Lucio: uma tradução transculturada e heterogênea - Thatiana Vasconcelos Barcelos (2013)
This work presents a Portuguese version of the story Cordillera Negra, written by the Peruvian author Oscar Lucio Colchado, followed by a critical study that aims at approaching the reflections and difficulties found in the process of translation. In this part, we discuss the relationship between translation and transculturation, in order to discuss its limits and borders. Therefore, in the field of translation, reflections of Antoine Berman about ethnocentric translation are considered, as well as Umberto Eco's about negotiation in translation; however for the discussion of transculturation, we analyze the Fernando Ortiz and Ángel Rama studies. The concept of cultural heterogeneity, by Antonio Cornejo Polar, is the main operator theory used in this dissertation that also seeks to analyze the relationship between memory and history and the limits of translation between Portuguese-Spanish within a context of bilingualism, mythology and oral expressions.